Transition from First Drug Use to Regular Injection among People Who Inject Drugs in Iran - Masoomeh Koozegar; Armita Shahesmaeili; Mehdi Noroozi (Addiction and Health, 2018)
Background: The study aimed to evaluate the interval between first drug use and regular injection and factors associated with transition from first injection into premature regular injection among people who inject drugs (PWIDs).Methods: In a multicenter cross-sectional study, we recruited 400 PWIDs using snowball sampling. Age of first drug use, age of initiation of regular injection, and demographic and behavioral data were collected using face to face interview. Premature transition to regular injection was defined as initiation of regular injection within the five years of first injection. Data were analyzed using bivariate and multivariate logistic regression survey analysis.Findings: The mean age of first drug use and age of initiation of regular injection was 29.87 ± 6.54 years, respectively. Having history of sexual abuse in childhood [adjusted odds ratio (AOR) = 3.1], history of imprisonment (AOR = 3.4), use of heroin as the first drug (AOR = 4.3), and doing the first injection at friends’ houses (AOR = 2.2) or in ruins (AOR = 2.2) significantly increased the chance of premature transition to regular injection, while being a female decreased the chance of premature transition to regular injection (AOR = 0.4). Compared to curiosity, being friend with a drug user (AOR = 0.4), having withdrawal symptoms (AOR = 0.2), and low cost of injection (AOR = 0.3) at the first occasion of drug injection reduced the chance of premature transition to regular injection.Conclusion: New interventions to prevent injection initiation among drug users are needed and should be integrated in harm reduction programs.